2013
DOI: 10.1371/journal.pone.0056534
|View full text |Cite
|
Sign up to set email alerts
|

A New Insect-Specific Flavivirus from Northern Australia Suppresses Replication of West Nile Virus and Murray Valley Encephalitis Virus in Co-infected Mosquito Cells

Abstract: Recent reports of a novel group of flaviviruses that replicate only in mosquitoes and appear to spread through insect populations via vertical transmission have emerged from around the globe. To date, there is no information on the presence or prevalence of these insect-specific flaviviruses (ISFs) in Australian mosquito species. To assess whether such viruses occur locally, we used reverse transcription-polymerase chain reaction (RT-PCR) and flavivirus universal primers that are specific to the NS5 gene to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
222
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(224 citation statements)
references
References 49 publications
2
222
0
Order By: Relevance
“…22 More recent studies in Australia with a newly described insect-specific flavivirus, PCV, showed suppression of WNV (Kunjin strain) and Murray Valley encephalitis virus replication in cells that were persistently infected with PCV. 21 Kenney and others 43 reported that Nahuirim virus, a newly characterized flavivirus from Brazil, reduces replication of WNV, Japanese encephalitis, and St. Louis encephalitis viruses in dually infected mosquito cell cultures. All of these in vitro experiments were conducted using C6/36 cells, which, unlike live mosquitoes, do not have a functional antiviral RNAi response, 44 thus the biological relevance of these in vitro results is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 More recent studies in Australia with a newly described insect-specific flavivirus, PCV, showed suppression of WNV (Kunjin strain) and Murray Valley encephalitis virus replication in cells that were persistently infected with PCV. 21 Kenney and others 43 reported that Nahuirim virus, a newly characterized flavivirus from Brazil, reduces replication of WNV, Japanese encephalitis, and St. Louis encephalitis viruses in dually infected mosquito cell cultures. All of these in vitro experiments were conducted using C6/36 cells, which, unlike live mosquitoes, do not have a functional antiviral RNAi response, 44 thus the biological relevance of these in vitro results is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…It is now apparent that these viruses are widespread in nature and that many are probably maintained by vertical transmission. [16][17][18][19] Some studies also suggest that superinfection exclusion (cells infected with one virus are refractory to infection by a second related virus) may occur between some insectspecific viruses and pathogenic arboviruses, 20,21 altering the vector competence of the mosquito host. In vivo and in vitro studies investigating interactions between two insect-specific flaviviruses (Culex flavivirus [CxFV] 20, 22 and Palm Creek virus [PCV] 21 ) with West Nile virus (WNV), have shown modulation of WNV replication and dissemination in dually infected mosquitoes, suggesting that some insect-specific viruses may alter the mosquito's ability to serve as a competent vector for certain pathogenic arboviruses.…”
Section: Introductionmentioning
confidence: 99%
“…These are believed to be vertically transmitted as they are not infectious by oral feeding (Bolling et al, 2012;Cook et al, 2012;Lutomiah et al, 2007;Saiyasombat et al, 2011). Interestingly, a number of them have been shown to negatively affect replication of medically important flaviviruses in co-infected or superinfected mosquitoes (Bolling et al, 2012;Goenaga et al, 2014;Hall-Mendelin et al, 2016;Hobson-Peters et al, 2013;Kenney et al, 2014).…”
mentioning
confidence: 99%
“…It is possible that ISF enhancement by Wolbachia may not have an effect on arboviruses (Crockett et al., 2012; Kent et al., 2010). Alternatively, it could lead to inhibition of arboviruses as was observed in the case of WNV and Murray Valley encephalitis (Bolling et al., 2012; Hobson‐Peters et al., 2013), further strengthening the pathogen blocking effect of Wolbachia . Given that ISF is common and widely distributed in Ae.…”
Section: Discussionmentioning
confidence: 97%
“…Since then, several others have been described including Culex flavivirus (CxFv) in Culex pipiens , Kamiti River virus in Ae. aegypti, and Palm Creek virus in Coquillettidia xanthogaster mosquitoes (Crabtree, Sang, Stollar, Dunster, & Miller, 2003; Hobson‐Peters et al., 2013; Hoshino et al., 2007). Even though ISFs are not directly associated with disease in vertebrates, there is growing interest in their effect on co‐infecting arboviruses.…”
Section: Introductionmentioning
confidence: 99%